TANGGUNG JAWAB RUMAH SAKIT TERHADAP KERUGIAN AKIBAT KELALAIAN TENAGA KESEHATAN DAN IMPLIKASINYA - Wahyudi, Setya (Jurnal Dinamika Hukum, 2011)
Justification hospital responsible for the losses resulting from the negligence of health workers in hospitals, namely the existence of the doctrine of respondeat superior, the doctrine of the hospital responsible for the quality of care (duty to care); and doctrine of vicarious liability, hospital liability, corporate liability. These doctrines are implemented on the provisions of Article 46 of Law Hospital in Indonesia, which determines that the hospital liable for all losses incurred on the negligence of health personnel in hospitals. The implications of the provisions was not easy for the public / patients to make compensation claims to the hospital, because it turns out there are reasons that can cause not all acts of negligence of health workers in hospitals is responsibility of the hospital. These reasons, such as health workers are not workers in the hospital; not know what parts are included in the therapeutic agreement with the doctor and what parts are included into the into the contract with the hospital.Key words: hospital responbility; negligence, health workers